Personal factors associated with digital competencies in university students in the context of pandemic - Uribe Hernández, Yrene Cecilia (2021)
The present research aimed to establish the association between personal factors (age, sex, hours connected and school of origin) and the digital competencies of university students, which have been originated and developed with a greater degree of intensity during the pandemic, generating as a consequence the need for distance education. The study was basic, explanatory, and quantitative, with a nonexperimental and cross-sectional design. The sample consisted of 1242 students of the Faculty of Medicine from the tenth to the fourth cycle: 658 males (53.0%) and 584 females (47.0%). A probabilistic sampling by strata was performed and the questionnaire of Gutiérrez et al. (2017), an instrument for the evaluation of the digital competence of the university student with a reliability of 0.997, was used. It was concluded that personal factors are associated with digital competencies in students of a private university because the personal factors of sex, age, school of origin and hours connected to social networks presented p < 0.05. Regarding descriptive results, 52.3% of male students presented ineffective level. Of students aged 22 years or younger, 58.2% presented an ineffective level. It was observed that 57.7% of the students who come from private schools presented an ineffective level, and 57.1% of the students who connect for 3 hours or less presented an ineffective level.